NEOPROTEROZOIC TO EARLY ORDOVICIAN EVOLUTION OF THE PALEO-ASIAN OCEAN: IMPLICATIONS TO THE BREAK-UP OF RODINIA - Dobretsov N.L.; Buslov M.M.; Vernikovsky V.A. (My University, 2003)
The paper reviews and integrates the recent geological and geochronological data, which allow us to recognize three stages of the evolution of the Paleo-Asian Ocean.The opening of the Paleo-Asian Ocean at 970-850 Ma is dated by the Nersin Complex in the Aldan shield, plagiogranites of the Sunuekit massif, enderbites of the Sludinsk Lake area, and passive margin sediments of the Patoma or Baikal series. The initial subduction (850-700 Ma) is marked by volcanic rocks, trondjemite and gabbro of the Sarkhoy island arc series. Collisions of microcontinents with Siberia at 660 to 620 Ma are evidenced by the exhumation of Muya eclogites (650 Ma), formation of migmatites and amphibolites of the Njurundukan belt (635 and 590 Ma), metamorphic units of the Near-Yenisei belt (640-600 Ma), and orogenic molasse (640-620 Ma). The Paleo-Asian Ocean maximally opened at 620-550 Ma, because at that time a long island arc composed of boninite volcanic rocks was formed. Primitive island arcs of that age have been reconstructed in Kazakhstan, Gorny Altai, West and East Sayan, and North Mongolia. HP and UHP rocks formed in two stages at 550-520 and 520-490 Ma. At 550-490 Ma oceanic islands and Gondwana-derived microcontinents (Kokchetav, Tuva-Mongolian, Central Mongolian and others) collided with the Cambrian-early Ordovician island arc of the Siberian continent. As a result, the island-arc system was extensively modified. Collision occurred twice at 550-520 and 520-490 Ma during which many HP and UHP rocks formed. At that time, the new oceans - the Junggar, Kazakhstan and Uralian - with an Ordovician island arc were formed.
Keywords: Tectonic evolution; accretionary and orogenic belts; Rodinia; Paleo-Asian Ocean; Ordovician; Neoproterozoic; Paleozoic::Ordovician; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Neoproterozoic; Палеозой::Ордовикская